Implementation of Blended Learning Policies During the Pandemic Covid-19 in Maluku Province - Patrisius Rahabav; Vando Chisty Nakaruku; Zeztrix Christina Rahabav (Peneliti.net, 2022)
The research objectives are 1) To find out the results and impact of the implementation of the bent learning policy in high schools and vocational schools in Maluku Province; 2) Identify supporting and inhibiting factors for the implementation of the bent learning pad policy in high schools and vocational schools in Maluku Province. The population of this research is all high schools and vocational schools in Maluku Province, totaling 395 schools with details: 282 high schools and 113 vocational schools. The sampling technique used, namelynon probability sampling. The type of sample used is a purposive sample. The data collection techniques used were questionnaires and interviews. Data analysis was carried out qualitatively and quantitatively. The results of data analysis show that overall the implementation of the blended learning policy in high schools and vocational schools in Maluku is in the medium category. The supporting factors for the implementation of blended learning, namely the level of participation and concern of parents in accompanying children in learning, are quite good. Parents have begun to realize their responsibility in their children's education. Teachers, students and parents have awareness of the importance of technology so that motivation to learn and use IT is increasingly high. Inhibiting factors: 1) lack of technology, limited infrastructure, 3) heavy burden of learning tasks, 4) limited funds, 5) teachers and students trapped in settingselektonic space. which has a negative impact, namely the attitude of individualism which impregnates social behavior, 6) decreasing quality and competitiveness.